TO DETERMINE THE CHANGE IN THE SIZE OF MACULAR HOLE DURING SURGERY BEFORE AND AFTER THE INTERNAL LIMITING MEMBRANE PEELING USING INTRAOPERATIVE OPTICAL COHERENCE TOMOGRAPHY (Journal of Medical & Health Sciences Review, 2025)
Background: Macular hole (MH) surgery has evolved significantly with the advent of intraoperative optical coherence tomography (iOCT), which allows real-time visualization of retinal architecture during key surgical steps such as internal limiting membrane (ILM) peeling.Objective: To determine the change in the size of macular hole diameter before and after ILM peeling using intraoperative OCT during macular hole surgery.Methodology: This prospective interventional study was conducted at LRBT, Tertiary Care Eye Hospital, Karachi, for six months, i.e, from 1st January 2023 to 30th June 2023, on 10 patients with idiopathic full-thickness macular holes undergoing standard 25-gauge pars plana vitrectomy with ILM peeling. Intraoperative OCT was used to measure the minimal MH diameter immediately before and after ILM peeling. Data was analyzed using SPSS version 26. A paired t- test was used with a significance of p ≤ 0.05.Results: The mean minimal MH diameter significantly decreased from 466.3 ± 75.1 µm before ILM peeling to 394.9 ± 40.5 µm after peeling (p = 0.0009). Most patients were female (60%) with a mean age of 61.3 years, and 50% were pseudophakic. A majority (60%) presented within three months of symptom onset.Conclusion: ILM peeling leads to a significant intraoperative reduction in macular hole diameter, confirming its role in relieving traction and facilitating retinal tissue approximation. iOCT provides a valuable tool for real-time assessment and may help predict surgical success.